2023
DOI: 10.1161/circoutcomes.122.009638
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Prenatal Diagnosis and Age at Surgery for Noncritical and Critical Congenital Heart Defects

Abstract: BACKGROUND: The relationship between the prenatal diagnosis of congenital heart defects (CHDs) and age at CHD surgery is poorly understood, despite the known relationships between age at surgery and long-term outcomes. The objective of this study was to determine the associations between prenatal diagnosis of CHD and age at surgery, and whether these associations differ for critical and noncritical CHDs. METHODS: This is a cohort analysis of patients ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Woo J.L. et al (30) demonstrated that prenatal diagnosis of CHD is associated with younger age at surgery, with consequences for long-term neurodevelopmental and physical outcomes. Prenatal diagnosis of patients with critical CHDs (hypoplastic left heart syndrome, D-transposition of the great arteries) allowed surgery to be performed one week earlier than for those diagnosed postnatally, and for patients with noncritical CHDs (noncritical coarctation of the aorta, VSD and ASD) the mean age at surgery was 2 to 15 months earlier than for children diagnosed postnatally.…”
Section: Discussionmentioning
confidence: 99%
“…Woo J.L. et al (30) demonstrated that prenatal diagnosis of CHD is associated with younger age at surgery, with consequences for long-term neurodevelopmental and physical outcomes. Prenatal diagnosis of patients with critical CHDs (hypoplastic left heart syndrome, D-transposition of the great arteries) allowed surgery to be performed one week earlier than for those diagnosed postnatally, and for patients with noncritical CHDs (noncritical coarctation of the aorta, VSD and ASD) the mean age at surgery was 2 to 15 months earlier than for children diagnosed postnatally.…”
Section: Discussionmentioning
confidence: 99%
“…However, using a previous dataset of children who received surgery at Lurie Children's between 2015 and 2021, we found prenatal diagnosis rates to be nearly identical before and during the pandemifc. 53 Our analysis excluded individuals who terminated their pregnancies, who may have experienced different barriers than those who experienced a live birth. Finally, our results may not generalize to other geographic areas.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Woo et al 3 aimed to establish whether prenatal diagnosis is definitively associated with surgery at an earlier age, both in critical and noncritical CHD lesions. The authors utilized advanced modeling techniques and analyzed clinically detailed data from the Society of Thoracic Surgeons Congenital Heart Surgery Database at Ann & Robert H. Lurie Children's Hospital of Chicago.…”
Section: See Article By Woo Et Almentioning
confidence: 99%